Underprivileged families and the incidence of stunted at birth in Sleman Regency based on the 2018-2019 Sleman Health and Demographic Surveillance System: a cohort study - Khistiyarini, Fifit; Helmyati, Siti; Purwaningrum, Digna Niken (BKM Public Health and Community Medicine, 2024)
Purpose: The incidence of stunting is a problem that needs to be resolved immediately. Stunting in children contributes to causing significant state losses, because the state must bear the costs of degenerative diseases as a result of the long-term impact of stunting. The family's economic status plays a role in the nutritional status of newborns. The purpose of this study was to determine the risk of stunted babies being born in underprivileged families. Methods: This study utilizes data from the 2019 Sleman Health Demographic Surveillance System (HDSS), employing a cohort method. The data used in this study went through the data-cleaning stage. The analysis carried out consisted of three things: descriptive, bivariate, and multivariable analysis. The number of samples used was 168. Results: The prevalence of stunting was 28.6%, and the prevalence of underprivileged families was 31.5%. The analysis revealed that babies born to disadvantaged families were 1.72 times more likely to be born stunted compared to babies born to prosperous families, as indicated by the multivariable analysis. Conclusion: The birth weight of babies is a significant factor influencing the incidence of stunted babies. Based on multivariable modeling, babies born to underprivileged families have a higher risk of being stunted, but this is not statistically significant. The same model shows that other variables that increase the risk of babies being born stunted are low birth weight (LBW).